The influence of ego-involving climates on perceived competence and commitment for U.S. Masters swimmers - Wineinger, Troy O.; Fry, Mary D.; Long, Haiying; Brown, Theresa C. (Frontiers in Psychology, 2025)
IntroductionThe climate adults experience in their sport and physical activity endeavors may be central for them staying active and promoting healthy aging. Researchers have focused on the adaptive effects of the task-involving climate on adults’ sport experiences, though little attention has been given to the maladaptive influences of an ego-involving climate.MethodsThe purpose of this study was to assess the relationship between Masters swimmers’ perceptions of an ego-involving climate, competence, and commitment, as well as investigate the moderating effect of perceived competence on Masters swimmers’ commitment within ego-involving climates. U.S. Masters swimmers (n = 566; Mage = 54.82; White 73.70%; female 67%) competing in coach-led programs completed an online survey.ResultsLatent moderated SEM analyses revealed that Masters swimmers’ perceptions of an ego-involving climate did not predict their sport commitment, although the interactive effect of an ego-involving climate and perceived competence was significant for commitment. Conditional effects further revealed that while athletes with higher perceptions of competence showed a positive relationship between ego-involving climate and sport commitment, a stronger negative association was observed for Masters swimmers with lower perceptions of competence in an ego-involving climate.DiscussionAdults, regardless of experience or expertise, can benefit from participating in physical activity and avoiding ego-involving tendencies is essential to fostering their commitment to staying active.